Phylogeny Influences Genome Size and GC but not Sequence and Organismal Complexity in Staphylococci - Ajay, Akash (Asian Journal of Biological and Life Sciences)
Aim: Like other ecological and morphological features, genomic features are adaptive and can be influenced by phylogeny. While some features like genome size and genomic GC have been explored in the past, still some features like genomic repeat fraction and protein-coding genes are unexplored. Understanding the trait evolution of the individual genomic features and how these features are related to each other is critical to evolutionary biology. Materials and Methods: This study investigates the trait evolution of genomic features in Staphylococcus, a bacterial clade having many pathogenic species and is of medical and pharmacological interest. Data on genome size, genomic GC, number of protein-coding genes, and genomic repeat fraction for species in Staphylococcus genus is collected and study their trait evolution and phylogenetic corrected relationships between them with the help of whole-genome phylogenetic trees. Results and Conclusion: We observe that the 4 genomic features studied follow differing trait evolution models genome sizes and genomic GC showing strong phylogenetic signal supporting the early-burst model, while the number of protein-coding genes and genomic repeat fraction show phylogeny-independent trait evolution. There is a significant negative correlation between genome size and genomic GC, indicating that addition of AT-rich sequences to the genome drove the increasing genome size during the early burst of diversification in Staphylococcus. The lack of correlation between the genome size with genomic repeat fraction and number of coding genes indicating the sequence complexity and organismal complexity evolved independently of genome size evolution in Staphylococci and repeat expansion may not have contributed to the genome size increase during the diversification.
Keywords: Phylogenetic conservation; Phylogenetic signal; Staphylococcus; Trait Evolution